Correlating complications of transurethral complications of prostate using the Charlson’s Comorbidity Index - Aditya Kumar (Society of Surgeons of Nepal, 2016)
Introduction: Ageing is a continuous, universal and progressive process associated with an increasing incidence of comorbidities. Benign Enlargement of Prostate (BEP) is major cause of morbidity in the ageing men. Transurethral Resection of Prostate (TURP) is the Gold Standard for patients with BEP and delivers durable outcomes, however, is associated with morbidity and mortality.This study was conducted to analyze the correlation of these comorbidities in ageing men with the incidence of complications of TURP.